PENGARUH POLA ASUH ORANG TUA TERHADAP DISIPLIN BELAJAR SISWA DI SMP NEGERI 1 X KOTO DIATAS KABUPATEN SOLOK - Dewi Fitri Yeni; Desi Armi Eka Putri; Ikhwan (STKIP Subang, 2024)
This research was motivated by the low learning discipline of students at SMP Negeri 1 This research aims to determine the influence of parenting patterns on student learning discipline at SMP Negeri 1 X Koto Above Solok Regency. This type of research is quantitative research. The population in this study were all students at SMP Negeri 1 Using the proportional stratified random sampling technique, the sample consisted of 115 students. The analysis technique used is a simple linear regression analysis technique. The results of this research show that parenting patterns with a significance level of 0.05 show that the influence of parenting patterns on student learning discipline at SMP Negeri 1 students at SMP Negeri 1 X Koto Above Solok Regency and the tcount value is 3.690 while the ttable is 1.658, so the hypothesis is accepted. The conclusion of this research is that there is a positive and significant influence between parental parenting patterns on student learning discipline. The suggestion in this research is to create rigid and compelling rules to regulate children at home, such as children having to complete school assignments before going out to play, children having to ask their parents for permission before going out, and limiting children's activities at home so that children do not get caught up in promiscuity. Keywords: Parenting Patterns, Student Learning Disciplin